ANALISIS KEUANGAN (FINANCIAL ANALYSIS) SEBAGAI SUATU CARA DALAM MELAKUKAN PENILAIAN PRESTASI KERJA KEUANGAN (PERFORMANCE) PERUSAHAAN (Studi Kasus Pada Perusahaan "PT. REVONA CIPTA PROPERTI") - Ike Ratnasari Putri; Budi Wahono; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThis study aims to determine whether the financial analysis can be used as a way of doing the assessment of financial work performance in real estate company PT Revona Malang. The selected research object is property company that is PT. RevonaCipta Property Malang with research period of 2012 until 2016. This research is replication of development and including research type Explanatory Reseach.Based on the ratio analysis it can be seen that the development of the general condition of the company from year to year has fluctuated in the sense that the company's ratio condition is down and up depending on the purchasing power of the people and the current economic policies as well as the ability of the company's management to apply its capabilities.With fluctuating assets used and with increased sales, the profit before taxes received by the company after 2014 should also increase. But it is unfortunate that the increased sales are not followed by a stable cost of goods sold. But it tends to increase. From the results of the study also can be seen that the variance of companies aimed through profit before taxes showed unfavorable variance. This means that the realization of planning of the company's activities is under the established budget.Keywords: Financial Analysis, Job Performance, Ratio Analysis